Reprints of Old Italian Books on Cookery and Food - Mussa, Carlo (Petits Propos Culinaires, 2024)
The author has an extensive collection of reprints and has kindly allowed us to reproduce particulars of them. This will serve as a useful checklist of what has been or still is available, and complements information which we have given in past issues about reprints of French and German cookery books. Carlo Mussa asks us, however, to make clear that his list is a personal one, not a comprehensive catalogue, and that he has not been able to indicate which of the reprints are still available from their publishers.